FORECASTING GRAIN CARGO HANDLING AT PORT ELEVATORS SOUTH-EASTERN REGION OF UKRAINE - Zinchenko, S; Stankevych, G; Sots, S; Zinchenko, H (Zernovì produkti ta kombìkorma, 2022)
The results of a study of the state and possibilities of increasing the capacity of grain transshipment in the ports of Ukraine and substantiation based on the developed trend models of forecast volumes of grain cargo transshipment in Berdyansk and Mariupol seaports of the South-Eastern region of Ukraine until 2025 are presented. The studies established the characteristics of grain cargo flows in the seaports of Ukraine, the SWOT analysis revealed the strengths and weaknesses, advantages and threats of the Mariupol Sea Trade Port, developed trend forecast models for grain transshipment volumes in the ports of the South-Eastern region of Ukraine and substantiated the forecast volumes of transshipment grain cargo until 2025. A rather uneven loading of the Mariupol port during the year is shown. August and all summer months are especially critical, when both industrial and agricultural goods need to be exported from the nearby region at the same time. The urgent need to increase the capacity of elevators for the ports of Chornomorsk, Reni and Olvia, as well as the ports of the Sea of Azov, in particular, the construction of a new elevator in the port of Mariupol, which is a timely strategic decision, has been substantiated. It was noted that at present most of the country's seaports are expected to increase the transshipment of food cargo of all kinds. To predict the volumes of transshipment of grain cargo at the Berdyansk and Mariupol seaports, based on the analysis of data from the state enterprise "Administration of the Sea Ports of Ukraine", forecast models (trends) are proposed that contribute to the growth of production capacity and competitiveness of agricultural products of the adjacent agro-industrial region. It is shown that the forecast for the next 2-4 years is optimistic – subject to a good grain harvest, the transshipment of grain cargo by 2025 in the Berdyansk and Mariupol ports can reach 2,000 and 1,300 thousand tons, respectively, that is, increase compared to 2021, respectively, 5 and 1.3 times. The conducted SWOT-analysis made it possible to identify and evaluate the factors influencing decision-making on the possibility of developing the Mariupol seaport. On the basis of analytical data, a long-term forecast was made for the further development of the transport and logistics component of the seaports of the South-East region of Ukraine, which will expand and improve port services aimed at increasing its throughput. Among the most important measures is the construction of an elevator in the Mariupol seaport, which will help increase the quality and safe transportation of agricultural products in the chain from the producer to the end consumer. The main measures aimed at increasing the competitiveness of the Mariupol port were identified, including: construction of complexes for transshipment of grain, containers, vegetable oil; dredging, construction of hydrotechnical bank protection structures; reconstruction of berths 2-4 and 14-15 of the port; reconstruction of the nearby railway station Mariupol-Port.